2011
DOI: 10.1097/wnf.0b013e31820a17f3
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Immunoglobulins Are a Therapeutic Option in the Treatment of Multiple Sclerosis Relapse

Abstract: Intravenous immunoglobulin did not show inferiority compared with IVMP in the treatment of an acute MS relapse evaluated clinically and radiologically. Therefore, we suggest that IVIG may be tried as a therapy in acute MS relapse, especially in case of contraindications to IVMP and plasmapheresis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 38 publications
0
19
2
3
Order By: Relevance
“…In the context of MOG 35-55 -induced EAE pathogenesis, this finding might be relevant, as recent evidence suggest that autoimmune-prone FcγRIIb-deficient mice exhibit more pronounced MOG 35-55 -induced EAE disease [60]. Importantly, intravenous Ig (IVIG) injection, which is reportedly therapeutic in MOG 35-55 -induced EAE [69] and has exhibited some evidence of efficacy in MS [70], may act by targeting the low-affinity IgG inhibitory receptor FcγRIIb [71]. Therefore, one could speculate that EndoS treatment in MOG 35-55 -EAE may have a dual anti-inflammatory activity, both inhibiting the activation of the complement and shifting the binding of pathogenic IgG toward the inhibitory action mediated through FcγRIIb.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of MOG 35-55 -induced EAE pathogenesis, this finding might be relevant, as recent evidence suggest that autoimmune-prone FcγRIIb-deficient mice exhibit more pronounced MOG 35-55 -induced EAE disease [60]. Importantly, intravenous Ig (IVIG) injection, which is reportedly therapeutic in MOG 35-55 -induced EAE [69] and has exhibited some evidence of efficacy in MS [70], may act by targeting the low-affinity IgG inhibitory receptor FcγRIIb [71]. Therefore, one could speculate that EndoS treatment in MOG 35-55 -EAE may have a dual anti-inflammatory activity, both inhibiting the activation of the complement and shifting the binding of pathogenic IgG toward the inhibitory action mediated through FcγRIIb.…”
Section: Discussionmentioning
confidence: 99%
“…[111][112][113][114][115][116][117] The humoral immune response may be particularly important when studying neurodegeneration. 1,4,[37][38][39][40][41]118 For example, patients with progressive disease are more likely to have B-cell follicle-like structures in the cerebral meninges.…”
Section: Antibodies As Contributors To Neurodegeneration and The Pathmentioning
confidence: 99%
“…However, the PRIVIG study also reported that the number of newly active lesions was lower and that the reduction of brain parenchymal volume was significantly smaller in an RRMS group with a high dose of hIgG (0.4 g/kg of bodyweight) than in a placebo group . There have also been reports showing the efficacy of hIgG for relapse prevention and the attenuation of acute exacerbation . Finally, it is important to note that the safety of disease‐modifying therapies, such as IFN‐β, glatiramer acetate and fingolimod, has not been fully confirmed in pregnant or breastfeeding patients with RRMS .…”
Section: Discussionmentioning
confidence: 99%